Method for producing cellulose nanofiber aqueous suspension
Patent Information
- Application Number
- JP2021160850
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-30
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2041-09-30
AI Technical Summary
【0009】 本発明により、セルロースナノファイバーの粉末を用いて、ゲル粒の残留の少ない水懸濁液を効率よく製造することができるようになる。より詳細には、懸濁時に低い回転数の撹拌機を用いた場合でも、セルロースナノファイバーの粉末由来のゲル粒の残留を低減させることが可能となる。低い回転数の撹拌機でも良好に懸濁できることにより、高回転数の撹拌機等の設備を持たない工場などにおいてもゲル粒が少ない懸濁液を製造することが可能となる。また、高回転数の撹拌機を用いる場合、液跳ねを起こして歩留まりが低下することがあるが、低回転数の撹拌機を用いることでそのような歩留まりの低下を抑制することができる。
Smart Images

Figure 0007645159000001 
Figure 0007645159000002 
Figure 0007645159000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an aqueous suspension of cellulose nanofibers. More specifically, it provides a method for efficiently producing an aqueous suspension with little residual gel particles by using cellulose nanofiber powder. [Background technology]
[0002] Cellulose nanofibers are fine fibers with a fiber diameter of about 3 nm to several hundred nm that have excellent dispersibility in aqueous media, and are expected to be used for maintaining the viscosity of foods, cosmetics, medical products, paints, etc., strengthening food raw material dough, retaining moisture, improving food stability, and as a low-calorie additive or emulsion stabilizing aid. However, when cellulose nanofibers in a state dispersed in water (wet state) are dried to form a dry solid, hydrogen bonds are usually formed between the fibers of the fine cellulose fibers, so even if water is added to this dry solid to redisperse it, it is generally difficult to redisperse it uniformly. For this reason, cellulose nanofibers are produced in a state dispersed in water (wet state), and are usually used for various purposes in a wet state without drying.
[0003] However, in order to keep this wet cellulose nanofiber stable, several to several hundred times the mass of water required relative to the mass of the cellulose nanofiber is required, which poses various problems such as the need to secure storage space and increased storage and transportation costs.
[0004] In response to the above problems, the applicant has proposed a method for improving the redispersibility of cellulose nanofiber dry solids by adding 5 to 300 mass% of a water-soluble polymer to anion-modified cellulose nanofibers to form a dry solid (Patent Document 1), and a method for improving the redispersibility of cellulose nanofiber dry solids by drying a mixture of cellulose nanofibers and a solvent using a vacuum drying device (Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2015 / 107995 [Patent Document 2] International Publication No. 2019 / 189318 Summary of the Invention [Problem to be solved by the invention]
[0006] The methods described in Patent Documents 1 and 2 are effective methods for producing a cellulose nanofiber dry solid with good redispersibility, but it is desirable to develop a new method that can efficiently produce an aqueous dispersion / suspension with fewer gel particles using a cellulose nanofiber dry solid.
[0007] The present invention aims to provide a new method for efficiently producing an aqueous suspension with minimal residual gel particles when producing an aqueous suspension using cellulose nanofiber powder. [Means for solving the problem]
[0008] As a result of intensive research, the inventors have found that when producing an aqueous suspension using cellulose nanofiber powder, by using a high shear viscosity aqueous solution produced by dissolving a thickening substance in water as a medium and suspending cellulose nanofiber powder in this aqueous solution, it is possible to produce an aqueous suspension with fewer residual gel particles even when a stirrer with a low rotation speed is used. An aqueous suspension obtained using a high shear viscosity aqueous solution as a medium has a high shear viscosity. The above-mentioned effect was confirmed when the shear viscosity of the aqueous suspension was 0.25 Pa s or more when measured at 25°C and a shear rate of 1560 (1 / s). The present invention includes the following. [1] A method for producing an aqueous suspension of cellulose nanofibers, comprising suspending a powder containing cellulose nanofibers in an aqueous solution of a substance having viscosity-increasing properties, wherein the shear viscosity of the aqueous suspension is 0.25 Pa s or more when measured at 25°C and a shear rate of 1560 (1 / s). [2] The method for producing an aqueous suspension of cellulose nanofibers according to [1], wherein the cellulose nanofibers are anion-modified cellulose nanofibers. [3] The method for producing an aqueous suspension of cellulose nanofibers according to [2], wherein the anion-modified cellulose nanofibers are cellulose nanofibers having a carboxyalkyl group or cellulose nanofibers having a carboxyl group. [4] The method for producing an aqueous suspension of cellulose nanofibers according to [3], wherein the anion-modified cellulose nanofibers are cellulose nanofibers having a carboxymethyl group and a degree of carboxymethyl substitution within the range of 0.01 to 0.50. [5] A method for producing an aqueous suspension of cellulose nanofibers according to any one of [1] to [4], wherein the powder containing cellulose nanofibers further contains carboxymethyl cellulose. [6] A method for producing an aqueous suspension of cellulose nanofibers described in any one of [1] to [5], wherein the thickening substance is sucrose and the concentration of sucrose in the aqueous solution is 60 mass% or more. [7] A method for producing an aqueous suspension of cellulose nanofibers according to any one of [1] to [5], wherein the thickening substance is dextrin and the concentration of dextrin in the aqueous solution is 50% by mass or more. [8] A method for producing a cellulose nanofiber aqueous suspension described in any one of [1] to [5], wherein the thickening substance is tamarind seed gum or carboxymethyl cellulose, and the concentration of the thickening substance in the aqueous solution is 1.5 mass% or more. [9] A method for producing an aqueous suspension of cellulose nanofibers according to any one of [1] to [5], wherein the thickening substance is a carboxyvinyl polymer, and the concentration of the carboxyvinyl polymer in the aqueous solution is 0.5 mass% or more. Effect of the Invention
[0009] According to the present invention, it is possible to efficiently produce an aqueous suspension with few residual gel particles using cellulose nanofiber powder. More specifically, even when a stirrer with a low rotation speed is used during suspension, it is possible to reduce the residual gel particles derived from the cellulose nanofiber powder. Since good suspension can be achieved even with a stirrer with a low rotation speed, it is possible to produce a suspension with few gel particles even in factories that do not have equipment such as a stirrer with a high rotation speed. In addition, when a stirrer with a high rotation speed is used, liquid splashing may occur and the yield may decrease, but such a decrease in yield can be suppressed by using a stirrer with a low rotation speed.
[0010] Furthermore, even when stirring is performed by hand using a whisk or stirring rod without using a stirrer, the use of the present invention makes it easier to obtain a suspension with fewer residual gel particles than when the present invention is not used.
[0011] Furthermore, since the present invention enables efficient suspension, it is believed that the time required for suspension can also be shortened. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention relates to a method for producing an aqueous suspension of cellulose nanofibers (hereinafter referred to as "CNF"). In detail, the method includes producing an aqueous suspension by suspending a powder containing CNF in an aqueous solution of a substance having a thickening property, and the shear viscosity of the aqueous suspension is 0.25 Pa·s or more when measured at 25°C and a shear rate of 1560 (1 / s). According to the present invention, an aqueous suspension of CNF with little residual gel particles can be obtained even when a stirrer with a low rotation speed is used. In the present invention, the terms "suspension" and "dispersion" are intended to have the same meaning unless otherwise specified, and are used interchangeably.
[0013] (Cellulose nanofiber) In the present invention, cellulose nanofibers (CNF) are cellulose raw materials such as pulp that have been refined to a fiber width on the nanometer level. The fiber width (average fiber diameter) of CNF is usually about 3 nm to several hundred nm, for example, about 3 to 500 nm. In the present invention, it is preferable to use CNF with an average fiber diameter of about 3 to 100 nm, and more preferably about 3 to 20 nm. The aspect ratio is 30 or more, preferably 50 or more, and more preferably 100 or more. There is no upper limit to the aspect ratio, but it is about 500 or less.
[0014] The average fiber diameter and length of CNF can be measured by analyzing 200 randomly selected fibers using an atomic force microscope (AFM) if the diameter is less than 20 nm, or a field emission scanning electron microscope (FE-SEM) if the diameter is 20 nm or more, and calculating the average. The aspect ratio can be calculated using the following formula: Aspect ratio = average fiber length / average fiber diameter.
[0015] CNF can be obtained by applying mechanical force to a cellulose raw material such as pulp described later to finely pulp (fibrillation). As the cellulose raw material, unmodified cellulose or pulp for papermaking, etc., as described later, may be used, or chemically modified cellulose obtained by further chemically modifying pulp for papermaking, etc., may be used. Examples of chemically modified cellulose include, but are not limited to, anion-modified cellulose in which an anionic group is introduced into the cellulose chain, and cation-modified cellulose in which a cationic group is introduced. Among these, it is preferable to use anion-modified cellulose. Anion-modified CNF can be obtained by fibrillating anion-modified cellulose to an average fiber diameter of less than 1 μm. The defibration method is not particularly limited, and known defibration devices such as high-speed rotation type, colloid mill type, high-pressure type, roll mill type, and ultrasonic type may be used. Among them, it is preferable to use a wet high-pressure or ultra-high-pressure homogenizer. Examples of anion-modified CNF include carboxyalkylated CNF with a carboxyalkyl group introduced, carboxylated CNF with a carboxyl group introduced, phosphate-esterified CNF with a phosphoric acid group introduced, and sulfate-esterified CNF with a sulfate group introduced. Among these, CNF having a carboxyalkyl group (carboxyalkylated CNF) or CNF having a carboxyl group (carboxylated CNF) is preferred.
[0016] (Cellulose raw material) Cellulose as a raw material for CNF is known to originate from plants, animals (e.g., ascidians), algae, microorganisms (e.g., acetic acid bacteria (Acetobacter)), microbial products, etc., and any of them can be used in the present invention. Examples of plant-derived cellulose include wood, bamboo, hemp, jute, kenaf, agricultural waste, cloth, and pulp (softwood unbleached kraft pulp (NUKP), softwood bleached kraft pulp (NBKP), hardwood unbleached kraft pulp (LUKP), hardwood bleached kraft pulp (LBKP), softwood unbleached sulfite pulp (NUSP), softwood bleached sulfite pulp (NBSP), thermomechanical pulp (TMP), recycled pulp, waste paper, etc.). In the present invention, cellulose fibers derived from plants or microorganisms are preferred, and cellulose fibers derived from plants are more preferred. The cellulose raw material may be chemically modified as described below. By miniaturizing the fiber width of the above-mentioned cellulose raw material or a cellulose raw material that has been chemically modified, such as anionically modified, (chemically modified cellulose) to the nanometer level, CNF or chemically modified CNF such as anionically modified CNF can be obtained.
[0017] (CNF with carboxyalkyl groups (carboxyalkylated CNF)) An example of anion-modified CNF is carboxyalkylated CNF having a carboxyalkyl group. In this specification, carboxyalkyl group refers to -RCOOH (acid type) and -RCOOM (metal salt type). Here, R is an alkylene group such as a methylene group or an ethylene group, and M is a metal ion. Among them, CM-modified CNF having a CM group in which R is a methylene group is most preferred. Carboxyalkylated CNF can be obtained by treating a cellulose raw material with a mercerizing agent and then treating it with a carboxyalkylating agent to obtain carboxyalkylated cellulose using a known method to introduce a carboxyalkyl group, and then defibrating the cellulose raw material.
[0018] The degree of carboxyalkyl substitution per anhydrous glucose unit of the carboxyalkylated CNF is preferably 0.50 or less. The lower limit of the degree of carboxyalkyl substitution is preferably 0.01 or more. In consideration of operability, the degree of substitution is preferably 0.02 to 0.40, more preferably 0.02 to 0.35, more preferably 0.10 to 0.35, more preferably 0.15 to 0.35, and even more preferably 0.15 to 0.30. The anhydrous glucose unit means each anhydrous glucose (glucose residue) constituting cellulose, and the degree of carboxyalkyl substitution indicates the proportion of hydroxyl groups (-OH) in the glucose residues constituting cellulose that are substituted with carboxyalkyl groups (-ORCOOH or -ORCOOM) (the number of carboxyalkyl groups per glucose residue). The degree of carboxyalkyl substitution can be adjusted by controlling the reaction conditions such as the amount of the mercerizing agent and the reaction time. The degree of CM substitution per glucose unit can be measured by the following method: Weigh out approximately 2.0 g of carboxylated CNF (bone dry) and place it in a 300 mL Erlenmeyer flask with a glass stopper. Add 100 mL of a solution of 100 mL of concentrated nitric acid in 900 mL of methanol and shake for 3 hours to convert the salt-type carboxylated CNF into hydrogen-type carboxylated CNF. Weigh out 1.5 g to 2.0 g of hydrogen-type carboxylated CNF (bone dry) and place it in a 300 mL Erlenmeyer flask with a glass stopper. Moisten the hydrogen-type carboxylated CNF with 15 mL of 80% by mass methanol, add 100 mL of 0.1 N NaOH, and shake at room temperature for 3 hours. Using phenolphthalein as an indicator, back-titrate the excess NaOH with 0.1 N H2SO4. Calculate the degree of carboxylated substitution (DS) using the following formula: A = [(100 × F'-(0.1N H2SO4) (mL) × F) × 0.1] / (bone dry mass of hydrogenated carboxylated CNF (g)) DS = 0.162 x A / (1-0.058 x A) A: The amount of 1N NaOH required to neutralize 1 g of hydrogenated carboxylated CNF (mL) F: Factor of 0.1N H2SO4 F': factor of 0.1N NaOH The degree of substitution of carboxyalkyl groups other than CM groups can also be measured by the same method as above.
[0019] In this specification, "CM-modified cellulose," which is a type of anion-modified cellulose used to prepare CM-modified CNF, and "CM-modified CNF" obtained by defibrating CM-modified cellulose, refer to those that maintain at least a part of their fibrous shape even when dispersed in water. Therefore, "CM-modified cellulose" and "CM-modified CNF" are distinguished from carboxymethyl cellulose (hereinafter referred to as "CMC"), which is a type of water-soluble polymer. When an aqueous dispersion of "CM-modified cellulose" is observed with an electron microscope, a fibrous substance can be observed. On the other hand, when an aqueous dispersion of CMC, which is a type of water-soluble polymer, is observed, no fibrous substance is observed. In addition, when "CM-modified cellulose" and "CM-modified CNF" are measured by X-ray diffraction, a peak of cellulose type I crystals can be observed, but cellulose type I crystals are not observed in the water-soluble polymer CMC.
[0020] (CNF with carboxyl groups (carboxylated CNF)) An example of anionic CNF is carboxylated CNF having a carboxyl group. In this specification, the carboxyl group refers to -COOH (acid type) and -COOM (metal salt type) (wherein M is a metal ion), or -COO - Carboxylated CNF can be obtained by obtaining carboxylated cellulose using a known method of oxidizing the hydroxyl groups of the pyranose rings of cellulose to carboxyl groups, and then defibrating the cellulose. Examples of the cellulose oxidation method include a method of oxidizing cellulose in water using an oxidizing agent in the presence of an N-oxyl compound such as 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO) and a bromide and / or iodide, and a method of oxidizing cellulose by contacting a cellulose raw material with a gas containing ozone as an oxidizing agent.
[0021] The amount of carboxyl groups in the carboxylated CNF is preferably 0.4 to 3.0 mmol / g, more preferably 0.6 to 2.0 mmol / g, more preferably 1.0 to 2.0 mmol / g, and even more preferably 1.1 to 2.0 mmol / g, based on the bone dry mass of the carboxylated CNF. The amount of carboxyl groups in the carboxylated CNF can be adjusted by controlling reaction conditions such as the amount of oxidizing agent added and reaction time. The amount of carboxyl groups can be measured by the following method: 60 ml of a 0.5% by mass slurry (aqueous dispersion) of carboxylated CNF is prepared, and a 0.1 M aqueous hydrochloric acid solution is added to adjust the pH to 2.5. Then, a 0.05 N aqueous sodium hydroxide solution is added dropwise to measure the electrical conductivity until the pH reaches 11. The electrical conductivity is calculated using the following formula from the amount of sodium hydroxide (a) consumed in the neutralization stage of the weak acid, where the change in electrical conductivity is gradual: Amount of carboxyl group [mmol / g carboxylated CNF] = a [ml] × 0.05 / mass of carboxylated CNF [g].
[0022] (Phosphate-esterified CNF) An example of anionic CNF is phosphoric acid esterified CNF. The phosphoric acid esterified CNF can be obtained by mixing a powder or an aqueous solution of a phosphoric acid compound with the above-mentioned cellulose raw material, or by adding an aqueous solution of a phosphoric acid compound to a slurry of the cellulose raw material, thereby introducing a phosphoric acid group derived from a phosphoric acid compound into cellulose to form phosphoric acid esterified cellulose, and then defibrating the cellulose. Examples of phosphoric acid compounds include phosphoric acid, polyphosphoric acid, phosphorous acid, hypophosphorous acid, phosphonic acid, polyphosphonic acid, and esters or salts thereof. Specific examples include, but are not limited to, phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium phosphite, potassium phosphite, sodium hypophosphite, potassium hypophosphite, sodium pyrophosphate, sodium metaphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium metaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, and ammonium metaphosphate. One or more of these compounds can be used in combination to introduce a phosphoric acid group derived from a phosphoric acid compound into cellulose. In this specification, the phosphoric acid group derived from a phosphoric acid compound includes a phosphoric acid group, a phosphorous acid group, a hypophosphorous acid group, a pyrophosphate group, a metaphosphate group, a polyphosphate group, a phosphonic acid group, and a polyphosphonic acid group. Phosphated cellulose and phosphoric acid esterified CNF include those in which one or more of these phosphoric acid groups are introduced into the molecular chain of cellulose. When reacting a cellulose raw material with a phosphoric acid compound, it is desirable to use the phosphoric acid compound as an aqueous solution, since this allows the reaction to proceed uniformly and increases the efficiency of the introduction of the above groups, and in this case, the pH of the aqueous solution is preferably pH 3 to 7. In addition, a nitrogen-containing compound such as urea may be added.
[0023] The degree of substitution of phosphate-based groups per glucose unit in the phosphated CNF (hereinafter simply referred to as "phosphate group substitution degree") is preferably 0.001 or more and less than 0.40. The degree of phosphate group substitution per glucose unit can be measured by the following method: A slurry of phosphorylated CNF with a solid content of 0.2% by mass is prepared. A strongly acidic ion exchange resin (Amberjet 1024; Organo Corporation, conditioned) is added to the slurry in an amount of 1 / 10 by volume, and the slurry is shaken for 1 hour. The slurry is then poured onto a mesh with 90 μm openings to separate the resin and slurry, thereby obtaining hydrogen-type phosphorylated CNF. Next, 50 μL of 0.1 N sodium hydroxide solution is added to the slurry after the ion exchange resin treatment once every 30 seconds, while measuring the change in the electrical conductivity value of the slurry. The amount of alkali (mmol) required in the region where the electrical conductivity drops sharply in the measurement results is divided by the solid content (g) in the slurry to be titrated to calculate the amount of phosphoric acid groups (mmol / g) per 1 g of hydrogen-type phosphorylated CNF. Furthermore, the degree of phosphoric acid substitution (DS) per glucose unit of the phosphorylated CNF is calculated by the following formula: DS = 0.162 x A / (1-0.079 x A) A: Amount of phosphate groups per gram of hydrogen phosphate esterified CNF (mmol / g).
[0024] (Sulfate esterified CNF) An example of anionic CNF is sulfated CNF. Sulfated CNF can be obtained by reacting the above-mentioned cellulose raw material with a sulfate compound to introduce a sulfate group derived from the sulfate compound into cellulose to form sulfated cellulose, which is then defibrated. Examples of the sulfate compound include sulfuric acid, sulfamic acid, chlorosulfonic acid, sulfur trioxide, and esters or salts thereof. Among these, sulfamic acid is preferably used because it has low solubility in cellulose and low acidity.
[0025] For example, when sulfamic acid is used as the sulfate compound, the amount of sulfamic acid used can be appropriately adjusted taking into consideration the amount of anion groups introduced into the cellulose chain. For example, it can be used in an amount of preferably 0.01 to 50 mol, more preferably 0.1 to 3.0 mol, per mol of glucose unit in the cellulose molecule.
[0026] The amount of sulfate groups per glucose unit in the sulfated CNF (hereinafter simply referred to as "amount of sulfate groups") is preferably 0.1 to 3.0 mmol / g. The amount of sulfate groups per glucose unit can be measured by the following method: The aqueous dispersion of sulfated CNF is subjected to solvent replacement with ethanol and then t-butanol, and then freeze-dried. 15 ml of ethanol and 5 ml of water are added to 200 mg of the obtained sample, and the mixture is stirred for 30 minutes. Then, 10 ml of 0.5N aqueous sodium hydroxide solution is added, and the mixture is stirred at 70°C for 30 minutes and then at 30°C for 24 hours. Next, phenolphthalein is added as an indicator, and the mixture is titrated with hydrochloric acid, and the following formula is used to calculate: Amount of sulfate group [mmol / g sample] = (5 - (0.1 x titration amount of hydrochloric acid [ml] x 2)) / 0.2.
[0027] (cation-modified CNF) Cation-modified CNF is CNF in which cationic groups have been introduced into the molecular chains of cellulose. Cation-modified CNF can be obtained by defibrating the cationic modified cellulose obtained by introducing cationic groups into the pyranose rings of cellulose to an average fiber diameter of less than 1 μm.
[0028] Cationically modified cellulose can be obtained by a known method in which the above-mentioned carboxylated cellulose is reacted with a cationizing agent such as glycidyl trimethylammonium chloride, 3-chloro-2-hydroxypropyltrialkylammonium hydrite or its halohydrin type, and an alkali metal hydroxide catalyst (sodium hydroxide, potassium hydroxide, etc.) in the presence of water or an alcohol having 1 to 4 carbon atoms, and the obtained cationically modified cellulose is defibrated to obtain cationically modified CNF.
[0029] The degree of cationic substitution per glucose unit in the cation-modified CNF is preferably 0.02 to 0.50. The degree of cationic substitution can be adjusted by the amount of the cationizing agent to be reacted and the composition ratio of water or alcohol having 1 to 4 carbon atoms. The degree of cationic substitution per glucose unit can be measured by the following method: After drying the cation-modified CNF, the nitrogen content was measured using a total nitrogen analyzer (TN-10 manufactured by Mitsubishi Chemical Corporation), and the degree of cation substitution (the average value of the number of moles of substituents per mole of anhydrous glucose unit) was calculated using the following formula: Degree of cation substitution = (162 x N) / (1-151.6 x N) N: Nitrogen content.
[0030] (Powder containing CNF) In the manufacturing method of the present invention, a water suspension of CNF is manufactured using the powder containing the above-mentioned CNF. In the present invention, "powder" refers to a dry solid obtained by drying until the moisture content is 0 to 15% by mass. The moisture content is preferably 0 to 10% by mass. When CNF is dried until the moisture content is such, it usually tends to become difficult to redisperse, but the method of the present invention improves redispersibility and makes it possible to reduce the amount of remaining gel particles even when a stirrer with a low rotation speed is used. The moisture content of the powder can be calculated using the mass (absolute dry mass) of the powder after drying at 105°C for 3 hours or more and the mass before drying.
[0031] The shape of the "powder" which is a dry solid is preferably a fine, homogeneous powder in consideration of ease of suspension, but it may also be in a form in which some of the powder aggregates to form lumps, or in a granular form.
[0032] The powder containing CNF can be produced, for example, but not limited to, by drying the dispersion containing CNF. The dispersion medium in the dispersion to be dried is not particularly limited, but is preferably water, a hydrophilic organic solvent, a hydrophobic organic solvent, or a mixed solvent thereof, and more preferably water or a mixed solvent of water and a hydrophilic organic solvent. The device used for drying is not particularly limited. For example, a vacuum drum dryer, a normal pressure drum dryer, a spray dryer, a hot air dryer, a warm air dryer, etc. can be used.
[0033] The "powder containing CNF" to be suspended in the present invention may contain other components in addition to CNF. For example, it may contain a powder of a water-soluble polymer to improve redispersibility. Examples of water-soluble polymers include cellulose derivatives (CMC, methylcellulose, hydroxypropylcellulose, ethylcellulose), xanthan gum, xyloglucan, dextrin, dextran, carrageenan, locust bean gum, alginic acid, alginates, pullulan, starch, potato starch, kudzu flour, modified starch (cationized starch, phosphorylated starch, phosphate crosslinked starch, phosphate monoesterified phosphate crosslinked starch, hydroxypropyl starch, hydroxypropylated phosphate crosslinked starch, acetylated adipate crosslinked starch, acetylated phosphate crosslinked starch, acetylated oxidized starch, sodium octenylsuccinate starch, starch acetate, oxidized starch), corn starch, and the like. Examples of the cellulose esters include gum arabic, gellan gum, polydextrose, pectin, chitin, water-soluble chitin, chitosan, casein, albumin, soy protein lysate, peptone, polyvinyl alcohol, polyacrylamide, polyacrylates, polyvinylpyrrolidone, polyvinyl acetate, polyamino acids, polylactic acid, polymalic acid, polyglycerin, latex, rosin-based sizing agents, petroleum resin-based sizing agents, urea resins, melamine resins, epoxy resins, polyamide resins, polyamide-polyamine resins, polyethyleneimine, polyamines, vegetable gums, polyethylene oxide, hydrophilic crosslinked polymers, starch-polyacrylic acid copolymers, tamarind gum, guar gum, colloidal silica, or mixtures of one or more of these. Among these, cellulose derivatives are preferred in terms of compatibility with CNF, and CMC and its salts are particularly preferred. It is believed that water-soluble polymers such as CMC and its salts penetrate between the fibers of CNF and increase the distance between the fibers, thereby improving redispersibility. Dextrin can also be preferably used as the water-soluble polymer.
[0034] When CMC is used as the water-soluble polymer, the CM substitution degree of the CMC is preferably in the range of 0.55 to 1.60, more preferably 0.55 to 1.10, and even more preferably 0.65 to 1.10. Since CMC having such a CM substitution degree dissolves in water, it does not maintain the shape of cellulose-derived fibers in water. As described above, "CMC" as a water-soluble polymer is distinguished from "CM-modified cellulose" that maintains a fibrous shape in water. In addition, "CM-modified CNF" obtained by defibrating "CM-modified cellulose" to an average fiber diameter of less than 1 μm is also distinguished from "CMC".
[0035] When a water-soluble polymer is blended with a powder containing CNF, the blending amount of the water-soluble polymer is preferably 5 to 300 mass% relative to the CNF (bone dry solid content), more preferably 20 to 300 mass%, even more preferably 25 to 200 mass%, and even more preferably 25 to 60 mass%.
[0036] In addition, the powder containing CNF may contain components other than CNF and water-soluble polymers, such as trace amounts of metal components, as long as the effects of the present invention are not impaired. (Aqueous solution of a substance with viscosity increasing properties) The method of the present invention includes suspending a powder containing CNF in an aqueous solution of a substance having a thickening property. The aqueous solution of a substance having a thickening property is an aqueous solution having a high shear viscosity by dissolving a substance having a thickening property in water, and is an aqueous solution having a shear viscosity of 0.25 Pa·s or more when measured at 25°C and a shear rate of 1560 (1 / s) of the finally obtained aqueous suspension. It has been found that by suspending a powder containing CNF in such an aqueous solution having a high shear viscosity, an aqueous suspension containing few residual CNF gel particles can be obtained.
[0037] The thickening substance that can be used in the present invention is a substance that can be dissolved in water and can achieve a high shear viscosity at a shear rate of 1560 (1 / s) by dissolving a certain amount in water. Examples of the thickening substance include sucrose, dextrin, tamarind seed gum, CMC, carboxyvinyl polymer, starch syrup (a mixture of maltose and maltotriose), guar gum, carrageenan, xanthan gum, locust bean gum, tara gum, cassia gum, glucomannan, gellan gum, pectin, psyllium seed gum, tragacanth gum, karaya gum, gum arabic, macrophomopsis gum, rhamsan gum, agar, alginic acids (alginic acid, alginate), curdlan, pullulan, cellulose derivatives (CMC, methylcellulose, hydroxypropylmethylcellulose, hydroxypropylcellulose, hydroxyethylcellulose, etc.), microcrystalline cellulose, fermented cellulose, gelatin, water-soluble soybean polysaccharides, starch, modified starch, polyethylene glycol, etc. Among these, sucrose, dextrin, tamarind seed gum, CMC, and carboxyvinyl polymers are particularly preferred.
[0038] The concentrations of these substances in the aqueous solution are not particularly limited. The concentrations may be such that the finally obtained aqueous suspension can achieve a shear viscosity of 0.25 Pa·s or more at 25°C and a shear rate of 1560 (1 / s) depending on the substance. For example, when sucrose is used, it is preferable to use an aqueous solution having a sucrose concentration of 60% by mass or more. When dextrin is used, it is preferable to use an aqueous solution having a dextrin concentration of 50% by mass or more. Similarly, in the case of tamarind seed gum or CMC, an aqueous solution having a concentration of 1.5% by mass or more is preferable, and in the case of carboxyvinyl polymer, an aqueous solution having a concentration of 0.5% by mass or more is preferable.
[0039] (Suspended) A powder containing CNF is suspended in an aqueous solution of the above-mentioned substance having viscosity-increasing properties to obtain an aqueous suspension of CNF. As mentioned above, in the present invention, the terms "suspension" and "dispersion" are intended to have the same meaning unless otherwise specified, and are used interchangeably.
[0040] The solid content concentration in the suspension of the powder containing CNF when the powder containing CNF is suspended in the above aqueous solution is not particularly limited. It can be said that the lower the solid content concentration of the powder in the suspension, the more uniformly the powder can be dispersed. However, even if the solid content concentration of the powder in the suspension is high, it can be said that a suspension with fewer residual gel particles can be obtained compared to the case where the above aqueous solution is not used. Therefore, the solid content concentration of the powder in the suspension may be appropriately set according to the application. For example, the solid content concentration of the powder in the suspension can be about 0.1 to 10.0% by mass, or about 1.0 to 6.0% by mass, but is not limited to these ranges.
[0041] In the case of suspension, for example, a stirrer such as a homomixer, homodisper, in-line mixer, juicer, industrial powder suction continuous dissolution and dispersion device, Henschel mixer, etc. can be used, but are not limited to these. When a powder containing CNF is suspended in an aqueous solution of high shear viscosity according to the method of the present invention, a suspension with fewer gel particles remaining can be obtained even when the rotation speed of the stirrer is low, compared to when the method of the present invention is not used. For example, even when stirring is performed by hand using a whisk or a stirring rod without using the above-mentioned stirrer, it can be said that a suspension with fewer gel particles remaining is more likely to be obtained compared to when the method of the present invention is not used. In this way, the present invention has the advantage that a suspension with fewer gel particles can be obtained even at a low rotation speed compared to when the present invention is not used. However, the use of a stirrer with a high rotation speed is not excluded. For example, when comparing stirring at the same rotation speed, the method of the present invention may be able to obtain a suspension with fewer gel particles in a shorter time than when the present invention is not used. Therefore, the rotation speed of the stirrer used for suspension in the present invention is not particularly limited. For example, while suspensions / dispersions have conventionally been produced using stirring / dispersing equipment with high rotation speeds of 3,000 rpm or more, or 12,000 rpm or more, it is now possible to obtain aqueous suspensions with fewer gel particles using stirrers with rotation speeds of around 600 to 800 rpm, although this is not limited thereto.
[0042] (CNF water suspension) The CNF aqueous suspension obtained by the present invention uses an aqueous solution with high shear viscosity (aqueous solution of a substance with thickening properties) as a medium as described above, and therefore has a shear viscosity of 0.25 Pa s or more when measured at 25°C and a shear rate of 1560 (1 / s). More preferably, it is 0.30 Pa s or more. There is no particular upper limit to the shear viscosity. Considering the ease of stirring during suspension, it is considered preferable that the shear viscosity is about 3 Pa s or less.
[0043] The shear viscosity can be measured, for example, using a rheometer (a viscoelasticity measuring device) as described in the Examples below. According to the present invention, the aqueous suspension obtained by suspending a powder containing CNF in an aqueous solution with high shear viscosity contains at least the CNF derived from the powder, the water-soluble polymer if the powder contains a water-soluble polymer, and the above-mentioned substance having viscosity-increasing properties in the water. Other substances may be contained in the water as long as they do not impair the effects of the present invention.
[0044] According to the present invention, the aqueous suspension obtained by suspending a powder containing CNF in an aqueous solution of high shear viscosity has fewer residual gel particles of CNF compared to an aqueous suspension obtained without using the method of the present invention. "Gel particles" are gel-like particles of aggregated CNF. The amount of gel particles remaining in the suspension can be evaluated, for example, using the method using a coloring material (such as ink drops) described in Japanese Patent No. 6769947. EXAMPLES
[0045] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. <Shear viscosity measurement> The temperature of the aqueous suspension was adjusted to 25°C, and the shear rate was adjusted to 1×10 -3 ~2×10 3It was logarithmically increased within the range, and the 60-point viscosity was measured at 5-second intervals. The shear viscosity at a shear rate of 1560 (1 / s) among the measurement results was described in the table.
[0046] <Evaluation of CNF gel particles remaining in the CNF aqueous suspension> The gel particles in the aqueous suspension were evaluated using the method of using ink droplets. This method makes it easier to confirm the presence or absence of aggregates (gel particles) of CNFs in the suspension that cannot be visually discriminated by adding a coloring material (ink droplets) to the CNF suspension and then observing it with an optical microscope. The evaluation method is specifically as follows: Two drops of ink droplets (manufactured by Take Sumi Co., Ltd., solid content 10%) were dropped into the aqueous suspension, and the scale of the rotation speed of the vortex mixer (Automatic Lab-mixer HM-10H manufactured by IUCHI Co., Ltd.) was set to the maximum and stirred for 30 seconds. The liquid after stirring was sandwiched between two glass plates so that the film thickness became 0.15 mm, and it was observed at a magnification of 100 times using an optical microscope (Digital Microscope VHX-6000 manufactured by KEYENCE Corporation), and images were taken at three locations. Those in which no gel particles were seen in the image were evaluated as "〇", those in which relatively small gel particles were about 20% in the image or large gel particles were about 10% were evaluated as "△", and those in which more gel particles were observed were evaluated as "×". For those of medium degree among 〇, △, and × due to unevenness at the observation points, etc., they were expressed as "△~〇", "×~△", etc.
[0047] <Experiment 1> A powder (water content 7 mass%) in which 40 mass% of CMC was mixed with CM-modified CNF (CM substitution degree 0.30) was used as the powder containing CNF.
[0048] 150 ml of ion-exchanged water was taken in a 600 ml container, and 1.5 g of the above powder was added. This was stirred at 3000 rpm for 60 minutes to obtain an aqueous suspension (Reference Example 1). Also, it was stirred at 600 rpm for 60 minutes to obtain an aqueous suspension (Comparative Example 1).
[0049] In addition, 75 ml of ion-exchanged water and sucrose (Mitsui Sugar Co., Ltd., white sugar) with the concentration shown in Table 1 were added to a 600 ml container and stirred with a homodisper. After the sucrose was dissolved, 0.75 g of the above powder was added and stirred at 600 rpm for 60 minutes to obtain an aqueous suspension (Comparative Example 2, Examples 1 to 3). The shear viscosity (25°C) at a shear rate of 1560 (1 / s) of the obtained aqueous suspensions of the Reference Example, Comparative Example, and Examples was measured by the method described above, and the CNF gel particles remaining in the aqueous suspension were evaluated by the method described above. The results are shown in Table 1.
[0050] [Table 1]
[0051] When sucrose was not added, no gel particles remained when stirred at 3000 rpm (Reference Example 1), but many gel particles were observed when stirred at 600 rpm (Comparative Example 1). In contrast, by adding sucrose, the amount of remaining gel particles decreased according to the amount of sucrose added.
[0052] <Experiment 2> Aqueous suspensions were prepared and evaluated in the same manner as in Experiment 1, except that tamarind seed gum (Natural Cosmetics Research Institute Co., Ltd.), carboxyvinyl polymer (Iwase Cosfa Co., Ltd.: Carbopol (registered trademark) 940 Polymer), CMC (Nippon Paper Industries Co., Ltd.: FS350HC), and dextrin (Matsutani Chemical Co., Ltd.: TK-16) were used in place of sucrose in the concentrations shown in Table 2. The results are shown in Table 2.
[0053] [Table 2]
[0054] Even when a substance other than sucrose was used as a thickening substance, it was confirmed that the amount of gel particles was reduced and the gel could be suspended well when the shear viscosity was 0.25 Pa·s or higher.
[0055] <Experiment 3> A powder containing CNF was used in which 40% by mass of CMC was mixed with carboxylated CNF (degree of CM substitution: 0.15) (water content: 10% by mass), and an aqueous suspension was prepared and evaluated in the same manner as in Experiment 1, except that the thickening substances used in Experiments 1 and 2 were used at the concentrations shown in Table 3. The results are shown in Table 3.
[0056] [Table 3]
[0057] Similar to the results of Experiment 1, when no thickening substance was added, no gel particles remained when stirred at 3000 rpm (Reference Example 2), but many gel particles were observed when stirred at 600 rpm (Comparative Example 7). In contrast, when the shear viscosity of the aqueous suspension was increased to 0.25 Pa s or higher by adding a thickening substance, a decrease in the amount of remaining gel particles was confirmed, similar to the results of Experiments 1 and 2.
Claims
1. A method for producing an aqueous suspension of anion-modified cellulose nanofibers, comprising suspending a powder containing anion-modified cellulose nanofibers in an aqueous solution of a substance having thickening properties, wherein the shear viscosity of the aqueous suspension is 0.25 Pa·s or more when measured at 25°C and a shear rate of 1560 (1 / s).
2. The method for producing an aqueous suspension of anion-modified cellulose nanofibers according to claim 1, wherein the anion-modified cellulose nanofibers are cellulose nanofibers having a carboxyalkyl group or cellulose nanofibers having a carboxyl group.
3. The method for producing an aqueous suspension of anion-modified cellulose nanofibers according to claim 2, wherein the anion-modified cellulose nanofibers are cellulose nanofibers having a carboxymethyl group and have a degree of carboxymethyl substitution in the range of 0.01 to 0.
50.
4. A method for producing an aqueous suspension of anion-modified cellulose nanofibers described in any one of claims 1 to 3, wherein the powder containing anion-modified cellulose nanofibers further contains carboxymethylcellulose.
5. The method for producing an aqueous suspension of anion-modified cellulose nanofibers according to any one of claims 1 to 4, wherein the thickening substance is sucrose, and the concentration of sucrose in the aqueous solution is 60% by mass or more.
6. The method for producing an aqueous suspension of anion-modified cellulose nanofibers according to any one of claims 1 to 4, wherein the thickening substance is dextrin, and the concentration of dextrin in the aqueous solution is 50 mass% or more.
7. The method for producing an anion-modified cellulose nanofiber aqueous suspension according to any one of claims 1 to 4, wherein the thickening substance is tamarind seed gum or carboxymethyl cellulose, and the concentration of the thickening substance in the aqueous solution is 1.5 mass% or more.
8. The method for producing an anion-modified cellulose nanofiber aqueous suspension according to any one of claims 1 to 4, wherein the thickening substance is a carboxyvinyl polymer, and the concentration of the carboxyvinyl polymer in the aqueous solution is 0.5 mass% or more.
Citation Information
Patent Citations
Production of porous cellulose particle
JP1997132601A
Water-dispersible cellulose and method for producing the same
JP2004041119A
Viscosity modifier
JP2016166258A
Fibrous substance fluid dispersion, and fiber-reinforced resin composition
JP2021066780A
Composition composed of highly dispersible cellulose complex and polysaccharide
WO2006062089A1